Structural Dynamics of the Employed Population of the Far Eastern Federal District of Russia - V. Moshkov , Anatoly (International Journal of Psychosocial Rehabilitation, 2020)
Currently, the Russian Federation is being introduced in integration and socio-economic processes unfolding in the dynamically developing Asia-Pacific region of the world. It is necessary to consider complex use of rich natural resource potential and favorable economic and geographical position as the most rational direction of development of the economy of the Far Eastern Federal District. The solution to this problem is closely related to the modernization of the existing industrial structure of the economy in the federal district. The study aims at investigating the impact of the current structure of employment (by type of economic activity) both in the Russian Federation as a whole and in individual subjects of the Far Eastern Federal District of Russia on the pace of economic development and the income level of the population. To that end, the article proposes to use the method of structural-share analysis, which allows assessing the degree of influence of national and local factors on the structure of employment by main types of economic activity of all 11 subjects of the district. It is noted that employment in the sphere of industrial production and services provides a high level of income.